Will “blue” be the new “green”? A futuristic perspective on marine built environments to combat climate change: Opportunities and risks - Ghada Mohammad Elrayies (Sustainable Futures)
The earth is reaching an unprecedented turning point due to the worsening consequences of climate change, especially rising sea levels, the inundation of densely populated coastal cities, and the associated threats in infrastructure. This has been accompanied by increased population density, scarcity of land-related resources, and increasing demand for low-carbon energy resources. To address these implications, our traditional approach to future urban planning must be re-evaluated and fundamentally redesigned. The vast expanse of ocean water has potential as a reliable source of renewable energy, providing carbon dioxide reservoirs and a source of food production; the oceans can solve current problems and be considered an asset for future generations. Although floating architecture has been proposed as a solution to sea level rise, there is a clear gap between the architectural proposals (design) and marine engineering solutions (technology). Furthermore, submerged architecture has not received its due share of research and investigation. This study thus aims to provide a reference and framework for designing self-sufficient ocean settlements (SSOSs) within a carbon-neutral vision, using a multidisciplinary approach to guide researchers and decision-makers. To this end, the literature published on issues related to the establishment of such settlements has been organized and analyzed in terms of design and technology in order to investigate the feasibility of establishing such types of oceanic human settlements by 1) highlighting their opportunities, 2) identifying their challenges, and 3) providing recommendations to address the challenges of community acceptance, environmental impact, cost, and maritime governance.